Technology-based marketing strategies through the consumer lens: how might perceptions of ethicality and effectiveness interrelate?. (20th January 2020) - Brooksbank, Roger; Fullerton, Sam; Miller, Steven
Today, digital technologies are being routinely incorporated within most companies' marketing strategies, and ongoing advancements mean that marketers are increasingly challenged as to which ones to deploy to best effect. Yet little research has sought to investigate the use of these technologies from a consumer perspective. Hence, a sample of 967 residents of the USA provided their perspectives in relation to 18 technology-based initiatives along two separate constructs: their ethicality according to society's moral norms, and their effectiveness as a mainstream marketing tool. This study focuses on measuring these constructs in order to explore how they might interrelate. Results indicate a wide spectrum of opinion as to what constitutes an ethical as well as an effective initiative and that, in general, the two constructs are positively correlated albeit not in equal measure on each scale. Findings further suggest the potential existence of three sub-dimensions of the ethicality-effectiveness correlation dyad.